How to manage dementia in general practice - Clarke, Nicholas [1961-]; Clarke, Farine; Edwards, Denzil [1954-] (Chichester, West Sussex, UK : Wiley-Blackwell/BMJ Books, 2013)
[electronic resource]
Includes bibliographical references and index.
This guide clearly shows each stage in the management of a patient with dementia. It covers the complex issues surrounding dementia such as spouses and families, access to appropriate care, legal and ethical concerns, planning for the future and ""living well"" and includes the decision making process on initiating treatment and guidance on how best to access the available services."
Diagnosing dementia in general practice -- Complex pictures of dementia -- Initiating, monitoring, and adjusting dementia treatments -- Emergency management of dementia -- Managing families -- Using the multidisciplinary team -- Capacity, consent, and deprivation of liberty -- Choosing a residential home -- Research, developments, and media coverage -- GP questions answered.